A Systematic Review of Efficacy of the Attention Training Technique in Clinical and Nonclinical Samples. Issue 10 (29th April 2016) - Knowles, Mark M.; Foden, Philip; El‐Deredy, Wael; Wells, Adrian
Abstract : Objective: The Attention Training Technique (ATT; Wells, 1990) is a brief metacognitive treatment strategy aimed at remediating self‐focused processing and increasing attention flexibility in psychological disorder. Method: We systematically reviewed and examined the efficacy of ATT in clinical and nonclinical samples. Scientific databases were searched from 1990 to 2014 and 10 studies (total N = 295) met inclusion criteria. Single‐case data were meta‐analyzed using the improvement rate difference, and standardized between and within‐group effect sizes (ESs) were examined across 4 analogue randomized controlled trials (RCTs). Results: Single‐case outcomes indicated that ATT yields large ES estimates (pooled ES range: 0.74–1.00) for anxiety and depressive disorders. Standardized ESs across the RCTs indicated that ATT yields greater treatment gains than reference groups across majority outcomes (adjusted Cohen's d range: 0.40–1.23). Conclusions: These preliminary results suggest ATT may be effective in treating anxiety and depressive disorders and help remediate some symptoms of schizophrenia. Although a limited number of studies with small sample sizes warrants caution of interpretation, ATT appears promising and future studies will benefit from adequately powered RCTs.